Acute and subchronic toxicity study of the water extract from dried fruits of Piper nigrum L. in rats - Chunlaratthanaphorn S. (2014)
The study was carried out to evaluate acute and subchronic toxicities of the water extract from the dried fruits of Piper nigrum L. A single oral administration of the extract at a dose of 5,000 mg/kg body weight (5 male, 5 female) did not produce signs of toxicity, behavioral changes, mortality, changes on gross appearance or histopathological changes of internal organs. The subchronic toxicity was determined by oral feeding both male and female rats (10 male, 10 female) daily with the test substance at the doses of 300, 600 and 1,200 mg/kg body weight continuously for 90 days. The examinations of signs, animal behavior and health monitoring showed no abnormalities in the test groups as compared to the controls. The test and control groups (on the 90th day) and the satellite group (on the 118th day) were analyzed by measuring their final body and organ weights, taking necropsy, and examining hematology, blood clinical chemistry and histopathology. The results suggest that the water extract from the dried fruits of P. nigrum does not cause acute or subchronic toxicities in either male or female rats.